Clarifying ethical responsibilities in pediatric biobanking. Issue 3 (2nd July 2016) - Spriggs, Merle; Fry, Craig L.
ABSTRACT: Background: The creation of biobanks for storage of human specimens and use in health and medical research is expanding globally. Biobanks hold significant potential to facilitate such research. However, important ethical questions arise, particularly in the pediatric setting, in relation to consent, future use, and the balance of benefits against potential harms. To date, these ethical issues have been undertheorized and underresearched in the biobanks domain. The aim of this study was to examine stakeholder attitudes regarding the ethical responsibilities of researchers, biobank custodians, Human Research Ethics Committees (HRECs), research institutions, and parents.Methods: A qualitative study using semistructured interviews with a purposive sample of key informants ( n = 14) with relevant expertise was conducted. Participants were interviewed about their pediatric biobank experiences, the main ethical issues observed as an HREC member, researcher, or custodian, and future needs.Results: Participants expressed concerns about consent processes in the biobanking context, including issues regarding the provision of information, level of understanding, voluntariness, and the point at which children have a role or can consent for themselves. Other major issues raised were biobank quality management, the return of results, and the idea of human tissue as a scarce precious resource. Key informants also highlighted uncertainties about the custodianship of biobank samples and reasonable limits on the custodian's role.Conclusions: Pediatric biobanks are a valuable resource, presenting unique opportunities to advance children's health and well-being. Properly run pediatric biobanks entail responsibilities for institutes, custodians, researchers, and research ethics committees. We discuss ethical implications for pediatric biobank policy and practices, as well as future information needs in light of the study findings.